The Sprawling Planet: Simplifying the Measurement of Global Urbanization Trends - Gerten, Christian; Fina, Stefan; Rusche, Karsten (Frontiers in Environmental Science, 2019)
The last decades have been characterized by a fast and steady urbanization of the global population. This trend is projected to stay stable in the future and affects land use patterns in multiple ways. Monitoring and measurement concepts for urbanization processes have struggled with the multitude of driving forces and variations in urban form as well as the assessment of outcomes on sometimes contradictory objectives for economic, social and environmental policies. Commonly, monitoring frameworks that aim to assess land use changes related to urbanization break this complexity down into singular dimensions that can be measured with individual indicators. Such monitoring allows planners and policy analysts to assess new urban growth against criteria of sustainable development. In this context we note that monitoring methods are most often designed for case studies in Europe or North America where urban structures are rather mature and consolidated. This paper presents an approach to simplify the measurement of land use changes related to urbanization with a new methodology. It condenses the needed measurement components to two dimensions: land use inefficiency and dispersion. The method can be rolled out globally based on the newly available Global Human Settlement layer available from the European Commission at no cost. In an initial application of the method to over 600 cities worldwide we show land use trends related to urbanization by continent and city size. In summary, we observe a consolidation of urban centers worldwide and continued sprawl in the outskirts. In European cities a consolidation phase of urban structures has started earlier, cities are more mature and develop less dynamically compared to other world regions. More in-depth analysis of case studies present results for the cities of Paris, France, and Chicago, United States. For Paris, the method helps to illustrate the growth pressures that led to massive urban sprawl in the outskirts with a continued densification of the inner city. For Chicago we detect a type of urban sprawl that goes along with waves of suburbanization with population loss in the inner city and continued urban sprawl in the outskirts that consolidated over time.